MESIN HOT EMBOSSING PALLET PLASTIK - Prayogi, Ais Sabastian; Tanjung, Ilham; Yuniarsih, Pratitis (Program Kreativitas Mahasiswa - Teknologi, 2013)
Automated hot embossing machine is aimed at generating concepts and design systems that are efficient, easy, precision and quality in the hot embossing machine plastic pallet and to develop standard operating procedures through the exact calculation. Making hot embossing machine based technology and automation. In hot embossing machine automatically, the operator simply presses a button and put the pallet and the operator of a security push button off as a protector in the framework of the machine operator. In terms of accuracy, speed, and accuracy more precise, faster and increase the amount of production . For embossing process used 6 kgf/cm2 pressure, temperature 100 Â° C and holding time 9 seconds. The material used for the frame type iron Hollo 40 st with size 600x600x5mm. Pneumatic cylinders are used for this machine is kind of a double acting cylinder with a diameter of 100 mm and 80mm has a production capacity of 30 pcs / hour . Hot embossing machine plastic pallet with electro - pneumatic system can improve the quality and productivity of the plastic pallet industry.